VIDEO RANCANGAN BY-PRO (SISTEM PENGUKURAN DAN PENDATAAN BALITA DI POSYANDU) - Chyntia Raras Ajeng Widiawati; Indra Alan Nugroho; Irfan Rifai Aziz; Rizky Arsyansyah (Jurnal Informatika, 2021)
Integrated Healthcare Center (IHC) activity is important thing to do to make sure the toddlers health by measuring toddler's weight and height. Recently IHC activity is done by using manual measurement tools that is sometimes dangerous for the toddler, and it's quite troubled for IHC cadre in reporting and organizing data. It's needed in designing product that can support continuity of IHC activities so it can run safety and comfortably. This research will design a product BY-PRO, a main solution to solve the problems. The design consist of Arduino microcontroller as data processor, cell load sensor (weight), optocoupler modul (height), and censor K02 (touch sencor) connected to Android via modul (Bluetooth) HC-05. Android Application can be used by IHC cadre to show identity data and toddler measurement saved to database and distributed to web-based Information System to monitor realtime health by midwife. The design result is presented in a video, so it can give an overview of the designed product.Keywords— Toddler Height Measuring, Toddler Weight Measuring, Android, Arduino, Bluetooth, Website, Posyandu